2009
DOI: 10.2174/1874372200903010044
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Extracellular Matrix Protein 1 (ECM1) in Maintaining the Functional Integrity of the Human Skin

Abstract: Abstract:The extracellular matrix protein 1 (ECM1) is an 85 kDa glycoprotein first identified in 1994. The threedimensional structure of ECM1 based on the third serum albumin domain was determined by in silico modelling in order to predict the most important binding site(s) of ECM1 with other protein partners in human skin. ECM1 consists of four domains: a first domain existing of -helices ( D1), the serum albumin subdomain-like (SASDL) domain 2, the sequence homology comparable with the first subdomain of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
(156 reference statements)
0
8
0
1
Order By: Relevance
“…This is the first detection of ECM1 expression in the aging heart. Previous studies have identified an inverse trend in the dermis where ECM1 expression decreases in aging human skin [41, 42]. This opposing finding is likely due to the fact that the aging of human skin is associated with decreased collagen and elastin content in the ECM leading to fragmentation and disorganization of the remaining collagen fibres [42, 43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first detection of ECM1 expression in the aging heart. Previous studies have identified an inverse trend in the dermis where ECM1 expression decreases in aging human skin [41, 42]. This opposing finding is likely due to the fact that the aging of human skin is associated with decreased collagen and elastin content in the ECM leading to fragmentation and disorganization of the remaining collagen fibres [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified an inverse trend in the dermis where ECM1 expression decreases in aging human skin [41, 42]. This opposing finding is likely due to the fact that the aging of human skin is associated with decreased collagen and elastin content in the ECM leading to fragmentation and disorganization of the remaining collagen fibres [42, 43]. In contrast, the aging heart is associated with the accumulation of collagen, elastin and other ECM proteins [38, 40], and a general shift in the expression of various matrix metalloproteinases (MMPs) [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM1 is suggested to act as biological glue capable of connecting the basolateral surface of the epidermis to the underlying dermis 23. It has the ability to bind to a number of extracellular matrix molecules, including collagen type IV, fibronectin, hyaluronic acid, chondroitin sulphate, matrix metalloproteases-9 (MMP-9), perlecan, laminin 332, fibulin-1C/D, fibulin-3 and heparin 24.…”
Section: Discussionmentioning
confidence: 99%
“…É provável que a diminuição da ECM-1 leve a um aumento da MMP-9 livre (Terlizzi et al, 2004). A MMP-9 livre por sua vez quebra o COL IV gerando fragmentos da cadeia alfa-3 de COL IV conhecido por tumistatina (Sercu et al, 2009). A tumistatina ativa TGF-beta que é conhecido por estimular a proliferação de fibroblastos e induzir a síntese e secreção de proteínas da matriz extracelular (Massague, 1998).…”
Section: )unclassified